A Rare Malignant Peripheral Nerve Sheath Tumor of the Maxilla Mimicking a Periapical Lesion - José Alcides Arruda; Pamella Álvares; Luciano Silva; Alexandrino Pereira dos Santos Neto; Cleomar Donizeth Rodrigues; Antônio Caubi; Marcia Silveira; Sandra Sayão; Ana Paula Sobral (Case Reports in Dentistry)
Malignant peripheral nerve sheath tumor is a malignant neoplasm that is rarely found in the oral cavity. About 50% of this tumor occurs in patients with neurofibromatosis type I and comprises approximately 10% of all soft tissue sarcomas of head and neck region. Intraosseous malignant peripheral nerve sheath tumor of the maxilla is rare. This article is the first to address malignant peripheral nerve sheath tumor of the maxilla presenting as a periapical radiolucency on nonvital endodontically treated teeth in the English medical literature. Surgical approaches to malignant soft tissue tumor vary based on the extent of the disease, age of the patient, and pathological findings. A rare case of intraosseous malignant peripheral nerve sheath tumor is reported in a 16-year-old woman. The patient presented clinically with a pain involving the upper left incisors region and with defined unilocular periapical radiolucency lesion involved between the upper left incisors. An incisional biopsy was made. Histological and immunohistochemical examination were positive for S-100 protein and glial fibrillary acidic protein showed that the lesion was an intraosseous malignant peripheral nerve sheath tumor of the maxilla. Nine years after the surgery, no regional recurrence was observed.